Perceived acceptability of progesterone to prevent preterm births and low birth weight among HIV-infected and HIV-uninfected Zambian pregnant women - Wong JMH; Kanga N; Dogra N; Ngoma MS; Serghides L; Silverman M (Dove Medical Press, 2017)
Jeffrey Man Hay Wong,1 Neha Kanga,1 Nupur Dogra,1 Mary Shilalukey Ngoma,2 Lena Serghides,3 Michael Silverman4 1Faculty of Medicine, University of Toronto, Toronto, ON, Canada; 2Department of Pediatrics, University of Zambia, Lusaka, Zambia; 3Toronto General Research Institute, University Health Network, Toronto, ON, Canada; 4Department of Infectious Diseases, Western University, London, ON, Canada Introduction: Intramuscular and vaginal progesterone are recommended for prevention of preterm labor (PTL) in women with risk factors. Studies are emerging to indicate that HIV-infected women on combination antiretroviral therapy (cART) are at risk of PTL and low birth weight (LBW), and may benefit from supplemental progesterone. This study aims to determine the perceived acceptability of various modes of progesterone supplementation to prevent PTL and LBW in HIV-infected and HIV-uninfected women.Methods: HIV-infected and HIV-uninfected women were recruited in Lusaka, Zambia. The participants completed a questionnaire to assess their willingness to take oral, vaginal, or intramuscular progesterone supplementation for preventing PTL and LBW, preferred modes of supplementation, and concern for PTL and LBW.Results: The study questionnaire was completed by 147 participants. Of the participants, 98.6% would consider using a medication to help prevent PTL and LBW, of whom 97.9% would consider using an oral form of progesterone. In addition, 83.3% and 84.0% of women would consider intramuscular and vaginal (gel or tablet) administration of progesterone respectively. Between intramuscular and vaginal modes of progesterone, 60.5% of participants (n=147) preferred intramuscular progesterone, while 39.5% preferred vaginal progesterone. There was no difference in preference between HIV-infected (n=70) and HIV-uninfected (n=77) women.Conclusions/implications: Pregnant Zambian women demonstrated a high degree of acceptance for all modes of progesterone supplementation for the prevention of PTL and LBW. Women preferred intramuscular over vaginal supplementation. Progesterone supplementation can be considered a feasible intervention for preventing PTL and LBW in both HIV-infected and HIV-uninfected pregnant Zambian women. Keywords: HIV/AIDS, progesterone, preterm labor, low birth weight, global health